Effects of a Dominant Species on the Functional Diversity of Coexisting Species in Temperate Deciduous Understorey - Krishan Kaushik; Alessandro Bricca; Michele Mugnai; Daniele Viciani; Kinga Rudolf; Katalin Somfalvi-Tóth; Tamás Morschhauser (Plants, 2021)
The herb layer plays a significant role in maintaining forest functions, and its community composition is determined by various abiotic factors and biotic interactions. This study attempted to investigate the interspecific plant–plant biotic interactions using a functional traits approach. Specifically, the effects of a dominant species coverage on the functional diversity of coexisting species in the temperate forest understory were studied. Species coverage and soil moisture data were collected using a 1 m2 quadrat couplet (2 × 1 m2) from six sites alongside a 20 m linear transect encompassing a cover gradient of Allium ursinum in southwest Hungary. Major plant functional dimensions i.e., aboveground, and clonal functional traits were considered. Linear and nonlinear mixed models to quantify the effects of biotic interaction on the functional diversity of every single trait and multiple traits were employed. Both aboveground traits and clonal traits of persistent clonal growth organs responded positively to the A. ursinum L., cover gradient. The coexistence of understory species in the presence of a monodominant species seems to be mainly influenced by aboveground traits as compared to the clonal traits suggesting, a role of niche differentiation. The consistent impact of A. ursinum coverage on coexisting species dynamics highlights a need for similar in-depth studies in various forest settings.